A Comparative Analysis of The Level of Banking Social Reports Disclosure in Indonesia (Islamic Social Reporting and Corporate Social Responsibility Approach) - Moh. Bahrudin; Ahmad Habibi; Muhammad Iqbal (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
This study aims to analyze the differences between conventional social reporting concepts of Corporate Social Responsibility (CSR) based on previous studies with the concept of Islamic Social Reporting (ISR) disclosure both in Islamic banks and conventional banks. The populations of this study are Islamic commercial banks and conventional banks. This study took 8 banks consisted of 4 Islamic banks and 4 conventional banks. The Independent Sample t-Test was used to analyze the data. The results of the study show that the use of the ISR index and CSR between sharia and conventional banks are different from each other in term of the companies’social report disclosure.